1967
DOI: 10.1037/h0024219
|View full text |Cite
|
Sign up to set email alerts
|

The doctor's voice: Postdictor of successful referral of alcoholic patients.

Abstract: 9 physicians discussed their experiences with alcoholics in tape-recorded interviews. Feelings and attitudes conveyed in doctors' speech were related to their success in referring alcoholic patients for treatment to a special clinic. 10 judges (5 male, S female) rated the interview material presented normally (unfiltered tape recording) ; 10 rated it presented in a "tone-only" condition (content-filtered tape recording); and 10 rated it in a "content-only" condition (typed transcripts). Doctors judged less ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0
1

Year Published

1971
1971
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(68 citation statements)
references
References 19 publications
3
64
0
1
Order By: Relevance
“…These channels may provide particular insights as to evaluative perceptions of distancing and anxious caregiver behavior. For instance, anxiety as judged from the vocal channel may communicate concern in a manner similar to the facial expressiveness composite examined in this article (Milmoe et al, 1967).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These channels may provide particular insights as to evaluative perceptions of distancing and anxious caregiver behavior. For instance, anxiety as judged from the vocal channel may communicate concern in a manner similar to the facial expressiveness composite examined in this article (Milmoe et al, 1967).…”
Section: Discussionmentioning
confidence: 99%
“…For example, ratings of anxiety from thin slices of physicians' voices predict their success in referring clients (Milmoe, Rosenthal, Blane, Chafetz, & Wolf, 1967). Other studies have shown that thin-slice ratings of physicians' behavior predict patient satisfaction (Hall, Roter, & Rand, 1981) and providers' expectations regarding clients .…”
Section: Thin-slice Judgments Of Nonverbal Behaviorsmentioning
confidence: 99%
“…There is little doubt that many of these provide redundant information and that emotional state can be correctly inferred from a very small set of vocal cues. Thus, it has been shown that emotions can be judged with better-than-chance accuracy from whispered speech (Knower, 1941;Pollack, Rubenstein and Horowitz, 1960), from speech samples that are played backwards (Knower, 1941) and from speech samples that have been content Filtered by cutting off the highfrequency band of the voice spectrum necessary for speech intelligibility (Soskin and Kauffman, 1961;Starkweather, 1956;Milmoe et al, 1967). The latter technique is of special interest since Mahi (1964) and Starkweather (1967) have argued that the lower frequencies of the voice are particularly important for the communication of emotional meaning, a statement that has received support from findings of Friedhoff et al (1964).…”
Section: This Research Was Supported By a Research Grant (Gs-2654) Frmentioning
confidence: 99%
“…Another investigator [20] attempted to relate doctors' feelings, as reflected in their speech during an interview, to the degree of success in referring alcoholic patients for continued treatment. The analysis involved auditing of tape recordings, content-filtered tape recordings (tone only), and transcripts of the in-terviews.…”
Section: The Study Of Communicationmentioning
confidence: 99%